The intertextual dialogue between Apollonius Rhodius’ Argonautica and the Homeric epic - Moreno del Cristo, Aluned (2020)
Apollonius Rhodius was one of the main figures of the Greek poetry in the Hellenistic period. In his only remaining work, Argonautica, this author established a significant dialogue with the previous literary tradition, especially with the Homeric epic. Due to the fact that, for many years, the study of Hellenistic literature has been neglected, and that, in addition, there has never been a comprehensive account of the relationship between Apollonius’ work and its epic antecedents, the purpose of this paper was to analyze intertextuality (specifically hipertextuality) between Argonautica and Homer’s poems. The examined aspects led to the conclusion that the Hellenistic poet conjugated within his work elements of tradition and innovation, and established a creative intertextual dialogue with the ancient oral poet, since at the same time that he assimilated masterfully the main methods and motives of traditional epic, he also incorporated the aesthetic devices of his own time. Keywords: Argonautica; Homeric epic; intertextuality; Hellenistic poetry.